(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Neonatal sepsis is a leading cause of neonatal mortality, and early identification of severity remains challenging in resource-limited settings. Red cell distribution width (RDW), a routinely reported haematological index, has emerged as a potential low-cost prognostic biomarker in sepsis. Objective: To evaluate the prognostic value of RDW in neonatal sepsis and its correlation with disease severity, and to identify associated risk factors. Methods: This prospective observational study enrolled 100 neonates aged 1–28 days with clinical features suggestive of sepsis to Koppal Institute of Medical Sciences, Koppal, India. Institutional ethical clearance and written consent from parents or guardian was taken. Neonates were classified as no sepsis, sepsis, or septic shock. RDW, complete blood count, CRP, and blood culture were assessed on day 1 and day 3 of illness. Sensitivity, specificity, and receiver operating characteristic (ROC) curve analysis were used to evaluate RDW as a predictor of CRP positivity. Results: Mean RDW increased with severity: 15.99 in neonates without sepsis, 17.43 in sepsis, and 18.25 in septic shock (correlation coefficient 0.49, moderate positive correlation). On day 1, RDW-CV (cut-off ≥16.00%) predicted CRP positivity with 88.9% sensitivity and 51.1% specificity (AUC 0.689, p=0.008), while RDW-SD (cut-off ≥66.30 fL) showed 50.0% sensitivity and 78.7% specificity (AUC 0.585, p=0.048). Blood culture was positive in 20% of neonates, most commonly Klebsiella pneumoniae (9%). Mortality was higher among outborn (20.3%) than inborn (12.2%) neonates. Conclusion: RDW rises progressively with the severity of neonatal sepsis and is a highly sensitive, inexpensive, and readily available screening biomarker. Its moderate specificity limits its use as a standalone diagnostic test, and it should be interpreted alongside CRP and clinical assessment. Larger multicentric studies are recommended to validate cut-off values before routine clinical adoption.